Esther Greenwood’s Alienation in Sylvia Plath’s The Bell Jar - DENNISA RETVIANDRA (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
Esther Greenwood’s Alienation in Sylvia Plath’s The Bell Jar Dennisa Retviandra English Literature Faculty of Languages and Arts Surabaya State University dennisandra13@gmail.com Drs. Much. Khoiri, M.Si. English Department Faculty of Languages and Arts Surabaya State University much_choiri@yahoo.com Abstrak Fokus skripsi ini adalah alienasi Esther Greenwood dalam novel semi-autobiografi karya Sylvia Plath berjudul The Bell Jar. Skripsi ini bertujuan untuk mengungkap alienasi yang dialami karakter utama, Esther Greenwood, dan untuk menjabarkan upaya Esther Greenwood dalam mengatasi alienasinya dalam novel The Bell Jar karya Sylvia Plath. Skripsi ini mencakup analisa mengenai bagaimana alienasi terwujud di tiap keadaan yang berbeda, pemicu terjadinya alienasi, serta strategi untuk mengatasi alienasi itu sendiri. Metode analisa deskriptif beserta teori alienasi dari Melvin Seeman, dan teori partisipasi dari Karol Wojtyla diaplikasikan di dalam pengerjaan skripsi ini. Dalam analisa data, teori ini digunakan untuk mengungkapkan alienasi yang dialami Esther Greenwood dengan menggolongkan isu alienasi tersebut menjadi lima kategori: yakni powerlessness, meaninglessness, normlessness, isolation, dan self-estrangement; serta menganalisa cara Esther Greenwood mengatasi alienasinya dengan beberapa upaya untuk berpatisipasi dengan masyarakat di sekitarnya. Hasil dalam skripsi ini menunjukkan bahwa alienasi Esther Greenwood mempengaruhi perilaku serta kondisi mentalnya. Perlahan namun pasti, alienasi membuat Esther Greenwood menjauh dari keadaan sosial di sekelilingnya. Dalam hal ini, alienasi yang muncul dalam kasus Esther Greenwood terlihat melalui beberapa gejala. Saat alienasi yang dialami Esther Greenwood memburuk, dia dibawa ke rumah sakit jiwa untuk pengobatan. Dalam hal ini, dengan bantuan psikiater pribadi, Esther Greenwood mengidentifikasi penyebab terjadinya alienasi yang ia alami dan perlahan-lahan pulih. Ia mulai berusaha untuk berpartisipasi dalam kegiatan dan hubungan yang berarti dengan sekitarnya. Kata Kunci: alienasi, powerlessness, meaninglessness, normlessness, isolation, self-estrangement, partisipasi Abstract This study focuses on Esther Greenwood’s alienation in Sylvia Plath’s semi-autobiographical novel entitled The Bell Jar. The purpose of this study is to depict the central character’s, Esther Greenwood, alienation and to describe how Esther Greenwood copes with her alienation in Sylvia Plath’s The Bell Jar. This study includes the analysis of how the alienation itself manifests in different ways, the triggers of alienation, as well as the strategy to overcome it. The study applies descriptive analysis method and the theory of alienation by Melvin Seeman, as well as the theory of participation by Karol Wojtyla. In the data analysis, they are used to analyze the alienation happened to Esther Greenwood by categorizing the issue into five senses: i.e. powerlessness, meaninglessness, normlessness, isolation and self-estrangement; as well as analyzing the way Esther Greenwood copes with her alienation by the several attempts to participate with society around her. The study finds out that Esther Greenwood’s alienation affects her in both behavior and mental state. Alienation slowly but sure distances her from the society around her. In this case, alienation that appears in Esther Greenwood’s case is seen through several symptoms. As Esther Greenwood’s alienation worsens, she is taken into the mental institution for treatment. In this case, with the help of private psychiatrist, Esther Greenwood herself identifies her root cause of alienation and slowly recovers. Later she maintains a particular way of participation in meaningful activities and relationship. Keywords: alienation, powerlessness, meaninglessne, normlessness, isolation, self-estrangement, participation INTRODUCTION In this 21ist century, novel is quite possible the most popular part of literature, in other words, novel is used for the sample literary application. Sylvia Plath regarded her only novel The Bell Jar as an “autobiographical work”. Semi-autobiographical means of or relating to a work that combines autobiography and fiction; “as semi-autobiographical novel” (Retrieved January 12, 2014, from http://dictionary.reference.com/browse/semiautoigra phical). From the definition above it can be concluded that semi-autobiographical novel is one of literary form, so it can be chosen as a data in this thesis for further study. The study of literature is no longer—if it ever was—simply the study and evaluation of poems, novels and plays. It is also the study of the ideas, issues and difficulties which arise in any literary text and in its interpretation (Parsons, 2007: viii). In this thesis, the novel which will be interpreted is The Bell Jar. In this thesis, the novel which will be interpreted is The Bell Jar. The Bell Jar is the only novel written by American poet and writer, Sylvia Plath. It is first published in London in January 1963 by Heinemann Limited, under the pseudonym “Victoria Lucas” for several reasons. Sylvia Plath was worried about the pain publication might cause to the many people close to her whose personalities she had distorted and lightly disguised in the book (Plath, 1963: 247), as it is a semi-autobiographical novel which many of the events were based on Sylvia Plath’s own life. So far, The Bell Jar has been translated into numerous languages. The Bell Jar was made into a film in 1979 directed by Larry Peerce, based on the novel, came up with the same title The Bell Jar, and in 2003 released a film based on Plath’s true story, starring Gwyneth Paltrow as Sylvia Plath, entitled Sylvia. Despite The Bell Jar is Plath’s only novel, it is one of the twentieth century’s best-known works. The Bell Jar records seven months in the life of Esther Greenwood. The story mostly takes place in New York city, Boston and its surrounding suburbs where the main action takes place in the summer of 1953. It is told that Esther Greenwood tries to conform to the sophisticated, urban world into which she has been inserted, she remains essentially withdrawn from it—and, more significantly, from herself. She finds herself increasingly apathetic about the writing and editing career she thought she wanted and from the life of success and privilege she thought she was pursuing. Isolated from the professional world unfolding around her, and from the mainstream of American life, she is also exiled from her own feelings and desires. The Bell Jar functions on many literary levels, but it is perhaps most obviously about the limitations imposed on young, intelligent American women in the 1950s. Moreover, this Plath’s only novel The Bell Jar dramatizes the collusion between the notion of a separate self (or bounded, autonomous subject) and the cultural forces that have oppressed women. The pervasive imagery of dismemberment conveys the alienation leading to main character’s, Esther Greenwood, breakdown. A German philosopher, Martin Heidegger, uses the Biblical metaphor of the Fall to describe this condition. In everyday social life we “fall” away from ourselves, into the world and into relations with others (Heidegger, 1962: 220). We are “dispersedd” in our involvements, lost in the world, dominated by the “they” (Heidegger, 1962: 1966-1967) In accordance, by alienation is meant a mode of experience in which the person experiences himself as an alien. He has become, one might say, estranged from himself (Fromm, 1955: 117). Alienation results when person cannot feel any rewarding satisfaction from his/her social involvement. It means that alienation results from guilt that has a social origin, from guilt that is generated by the social roles that the person has to play. Nonetheless, based on facts lay on the background of the study above, then the problem are emerged and divided into three: (1) how is Esther Greenwood’s alienation depicted in Sylvia Plath’s The Bell Jar? (2) what is the root cause of Esther Greenwood’s alienation in Sylvia Plath’s The Bell Jar? and (3) what is Esther Greenwood’s strategy to cope with her alienation in Sylvia Plath’s The Bell Jar? As referred to the background and statement of the problems above, the objectives of the study are devoted to know three purposes as results of analyzing the problem: (1) to depict Esther Greenwood’s alienation in Sylvia Plath’s The Bell Jar (2) to describe the root cause of Esther Greenwood’s alienation in Sylvia Plath’s The Bell Jar and (3) To describe Esther Greenwoood’s strategy to cope with her alienation in Sylvia Plath’s The Bell Jar. In accordance, it is expected that this study can give both theoritical and practical significance. In theoritical significance, on the most common interpretations of Sylvia Plath’s The Bell Jar, sees Esther Greenwood’s life as an example of the difficult position of educated women in America in the 1950s. It raises the issue of alienation. Esther’s dissatisfactions of herself and also her life may be typical of well-educated American women of her generation. Yet, Esther does not imagine herself as part of a community and identify herself in contrast to other women as well. Specifically in this study, through the analysis of main character in the novel, it will reveal about the process and cause of alienation matter. Therefore, this study is intended to give a meaningful contribution for a better understanding and deep comprehension of alienation. Additionally, in practical significance, this study can obtain positive contribution towards the development of analyzing literary works, which studies literature and society under the concept of alienation. This significance is hopefully merit for students, lecturers, and institution. Hopefully, to whom this study may concern, it can be utilized as reference, especially those who conduct studies upon sociology of literature under the concept of alienation. Besides, as reference, it can be used as model or media in studying and applying the above concept when analyzing the literary works. Furthermorre, this study hopefully can assist the institution to provide rich collection of research references. RESEARCH METHOD A method is always needed as a tool while technique is the way a tool (method) is used to solve the existed problems (Ratna. 2004: 34-37). Therefore, based upon the objectives of study above, this stuy will be analyzed by using descriptive analysis method. This method, Ratna explains further, is use to analyze a problem by describing the facts that contained in the object of the study and then analyzing it with the specific aim to give best explanation and understanding (Ratna, 2004: 53). Moreover, in this research method also comprises three parts, which are data source, data collections, and procedure of analysis. The first part is data source. The data source is taken from a semi-autobiographical novel entitled The Bell Jar written by Sylvia Plath. Published in New York, the book is reissued as 50th anniversary edition by HarperCollins Publishers in 2013 (Harper Perennial Modern Classic deluxe edition) with eISBN-13: 978-0-06-114851-4 and eISBN-10: 0-06-017490-0, and foreword by Frances McCullough. The second part is data collections. Data are quotations taken from the novel which includes narration and the characters’ dialogue and action in the novel that reflects the objective of the study, Esther Greenwood’s alienation and how she tries to cope with it. In collecting data, there are three steps to be accomplished. First of all, the beginning step to derive the data is by close reading the novel entirely. It is done over and over in order to be able to catch and understand the core story—intrinsically and extrinsically—of the novel. Besides, it also aims to support collecting and analyzing the objectives of the study later on. Secondly, it comes to the step where data is collected through noting the narration and characters’ dialogue and action in the novel, which reflects the idea of the central character’s alienation and the attempts on coping with it in the form of quotation. Thirdly, then it comes to the step of classifying data. The classification of the collected data is divided into three parts relating according to the three objectives of the study—the data which represents the case of Esther Greenwood’s alienation, as well as the other data which reflects the root cause of alienation and how she tries to cope with it—in order to ease observing the story. The last part is procedure of analysis. Here, to simplify the analysis of the stuy, there are also important steps needed to be done. The first is decribing the facts. At this point, the facts are the data in the novel which supports the study of the objectives of the stuy. It is done by describing the collected and classified data based on the subject of this study—Esther Greenwood’s alienation, the triggers of alienation, and how she copes with alienation. The description will touch upon mentioning the detail of the subject, how alienation is experienced (through how society affects and leads to this behavior) an the attempts to cope with it (by finding the root caue with the help of psychiatrist, and soon). Last but not least, the second is doing the analysis towardss the described data. It will dig the information beyond the data deeper by explaining it thoroughly. It is taken from the data in the novel first and, then, it will be analyzed by based on the thought of researcher. At this point, to make best explanation and understanding of the study, it will relate the data with acceptable theory and concept of alienation and other references taken from library and internet to support the analysis. ALIENATION In general, based on fields and domains of research, the concepts and theories of alienation can be classified into two theoretical domains of sociology and psychology. Although there is not a complete agreement and unanimity between sociologists about the meaning of alienation, it is obvious that they have complete agreement about the role of social external factors in emergence of alienation (Tabrizi, 1991: 1-2). Melvin Seeman, an American sociologist, has made his best in developing the concept of alienation, explaining its links, and suggesting a more precise definition of alienation. In On The Meaning of Alienation (1959), Seeman explains the case of alienation taken from the social-psychological point of view. He devided alienation into five senses: i.e. powerlessness, meaninglessness, normlessness, isolation, and self-estrangement. Powerlessness is a state in which the individual has some expectations but he supposes that cannot afford meeting them. Meanwhile alienation in the sense of meaninglessness happens when the individual cannot identify any meaning for his action; as a result, the outcomes of his action cannot be predicted. This refers to the individual’s sense of understanding the events in which he is engaged. The third is normlessnesss. Normlessness may occur where the disciplining effect of collective standards has been weakened. The fourth refers to isolation. That is isolation from the society when the individual does not respect the social norms seclusion takes place. The last one is alienation in the sense of self-etsrangement. Seeman refers to the aspect of self-alienation which is generally characterized as the loss of intrinsic meaning or pride in work. THE ROOT CAUSE OF ALIENATION Karol Wojtyla in Theory of Participation (1995) says alienation is a problem and a hindrance to a person’s fulfillment through his actions. Alienation can be caused by the person to himself or it can be done to him by society or it could be a combination of both. In Wojtyla’s analysis of alienation, he presents two prevalent systems that foster it: invidualism and totalism. Individualism is a system that puts high emphasis on the individuality of persons. Wojtyla explains that individualism sees in the individual the supreme and fundamental good, to which all interests of the community or the society have to be subordinated. Individualism isolates the person from others as an individual who concentrates on himself and on his own goods. As priority is given to individual goods, individualism also considers community goods as threat to the individual. The opposite of individualism is totalism. This system is a reversal of individualism in the sense that the individual is seen as a threat to the good of the community. The dominant trait of totalism is characterized as the need to find protection from the individual, who is seen as the chief enemy of the society and the common good (Mejos, 2007:77). As the opposite of individualism, it works under the assumption that all the goods that the individual is seeking are only individual goods and thus are understood as an obstacle to the common good. The good of the individual must be put aside for the sake of the common good. The common good can only be achieved if the individual is limited. PARTICIPATION: A STRATEGY TO COPE WITH ALIENATION Wojtyla’s answer to the problem of alienation is his theory of Participation. This theory is described as a property of the person as well as an ability to share in the humanity of others. It means that the theory affirms the fact that man exists and acts together with others. Wojtyla reveals the word “participation” to indicate the way in which, in common acting, the person protects the personalistic value of his own acting and participates together in the realization of common action and its outcomes. Participation points to the ability of the person to exist and act together with others without losing oneself as he moving towards his self-fulfillment. The participation itself takes different forms. Wojtyla in his Theory of Participation (1995) differentiates into two forms which are solidarity and opposition. Solidarity means a constant readiness to accept and to realize one’s share in the community because of one’s membership within that particular community (Wojtyla, 1979: 285). Solidarity expresses the unity of the parts (members) in their pursuit of the common good. Persons who are linked together in the attitude of solidarity realize the fact that they are members of a group and that they have to work together to achieve the good of the group. Opposition is not the opposite of solidarity but is another mode of it. Opposition means to oppose something for the sake of the common good. Opposition is when, in the name of participation, one opposes what is or what one judges to be contrary to the common good. There are many goods that are presented as apparently common. The attitude of opposition is borne out of the recognition that there is a need to defy from the apparent common good for the sake of the real common good (Mejos, 2007: 81). Opposition does not mean the denial or the withdrawal of the person in pursuit of the common good. But it is a result of their recognition of the common good. ESTHER GREENWOOD’S ALIENATION The occurrence of Esther Greenwood’s alienation depicted in the story manifests in different ways. In this case, Esther Greenwood’s alienation manifest in five senses; those are powerlessness, meaninglessness, normlessness, isolation, and self-estrangement. Esther’s alienation in the sense of powerlessness can be seen on her jealousy of unable to experience such luxuries which the other girls have, since Esther is only raised in the middle-social-background family (Plath, 1963: 4). This sense of powerlessness traps Esther into jealousy to socially estranged. She self-consciously distances herself from the other girls. Esther feels overwhelmed and powerless to break free the emotional burdens of status and social class difference. As a result, she does not get along very well with the social world around her. Life is also viewed as meaningless if Esther does not have her own identity and freedom. Trapped as well inside this meaninglessness sense of alienation, she feels all of her working life seems dominated by piles of meaningless manuscripts, compared the way that people around her are living it in luxury, the thing that she never has (Plath, 1963: 29). As a result, Esther does not find any purpose and goal to even act any single action as she feels indecisive all the time. Furthermore, Esther’s alienation in the sense of normlessness appears when she is against the conventional attitude of what a woman’s place in society is. It can be seen that Esther, unlike many women of her time, refuses to be controlled by society’s gender-based constraints. She decies not to marry (Plath, 1963: 76), not to have children, to have sexual freedom (Plath, 1963: 90), and to be a different kind of woman than what the society norm would wish for. She is so determined where her concerns are different, as well as her obstacles, especially in the general of social-ethos in 1950s America. In the other side, Esther’s isolation is implicitly depicted even on the meaning of the title The Bell Jar itself. Plath chooses this imagery which holds a perfect key to reveal Esther’s isolation. Here, the bell jar is viewed as a symbol of society’s stifling constraints and confusing mixed messages that trap Esther within its glass dome. Esther has her own “bell jar”, where she feels isolated all the time. To complicate the matters more, Esther’s sense of isolation is worsen when she loses interest in both social life and her work (Plath, 1963: 31-32). The last but not least is Esther’s alienation in the sense of self-estrangement. This is where Esther herself unsure about her true identity. She has sense of inner absence, vacuity, a loss of self or estrangement from a familiar and recognizable self. And thus she becomes a stranger in society and, more importantly, to herself. The more self-estranged Esther becomes, the less attached she is to her real wants, needs, hopes, and dreams. As a result, this sense of self-estrangement prevents Esther to find a real joy in life (Plath, 1963: 2). ESTHER GREENWOOD’S ROOT CAUSE OF ALIENATION As mentioned before, in Esther’s case, the alienation itself manifests in five different senses; powerlessness, meaninglessness, normlessness, isolation, and self-estrangement. She feels alienated by the expectations placed on her shoulders. The society’s norms expect her to snuggle down and marry a suitable husband, while Esther wants to write and explore life that societal norms denies her. Esther’s individualism is mostly shown when Esther consciously distances herself from the era’s “domestic containment” of women. When Esther’s domineering boyfriend, Buddy Willard, tells her that “what a man wants is a mate and what a woman wants is infinite security” and “what a man is is an arrow into the future and what a woman is is the place the arrow shoots off from” (Plath, 1963: 72), Esther negatively reacts to such gender clichés. Buddy learned his clichés from his mother, who once spent weeks braiding a beautiful multicolored rug but then used it as a kitchen mat, “and in a few days it was soiled and dull” (Plath, 1963: 85). Esther comes to believe that, despite the romantic thrill of marriage, a man secretly wanted his wife “to flatten out underneath his feet like Mrs. Willard’s kitchen mat” (Plath, 1963: 85). Esther also realizes that while Buddy is intelligent, he is not particularly thoughtful. She recalls Buddy saying “in a sinister, knowing way” that after she had children she “wouldn’t want to write poems any more” (Plath, 1963: 85). He does not understand Esther’s desire to write poetry, telling her that poems are like dust, and that her passion for poetry will change as soon as she becomes a mother. Esther is afraid if such a marriage would destroy her creative desire. She begins to fear that “when you were married and had children it was like being brainwashed and afterward you went about numb as a slave in some private, totalitarian state” (Plath, 1963: 85). Meanwhile, Esther’s alienation is also caused by her surroundings. In this case, it is ironically caused by her own boyfriend, Buddy Willard, as well. Buddy is a perfect example of society’s totalism. Buddy ignores Esther’s attempts to vision a future and pushes Esther to fit in the social norm in which she is not even his wife. For example, when Esther tells Buddy, “I'm never going to get married”, his face brightens and he suggests, “you’ll change your mind” (Plath, 1963: 93). Even as Esther protests that her decision is final, Buddy disregards her objections to marriage, as he mentally paves over the possibility of Esther’s rejection of domesticity. His firm desire to contain Esther in the role of wife and mother becomes evident when he delights in an injury that forces her to wear “a cast for months” (Plath, 1963: 98). After Esther breaks her leg on a ski slopes, “a queer, satisfied expression came over Buddy’s face” (Plath, 1963: 98). He smiles at this moment, and seems to take some pleasure in the harm that is happened on Esther. His happiness no doubt relates to the fact that this injury consigns Esther to the home and temporarily prevents her from exploring alternate possibilities for her future. This presents the fact that Buddy accepts his mother’s conventional ideas about how he should organize his domestic and emotional life even more. Another cause of Esther’s alienation is her fraught relationship with her parents. Her mother, though superficially caring and picture perfect, functions as a subtle force of control and reproach. Esther’s mother insists that her daughter channel herself into socially acceptable directions without paying attention to Esther’s own needs. As a result, Esther makes a point of “never living in the same house with my mother for more than a week” (Plath, 1963: 118). When she does live with her mother after returning from New York, she adopts a “hollow voice” that becomes a “zombie voice” as her mental illness worsen (Plath, 1963: 118-119). Esther even says she hates her mother (Plath, 1963: 203). Two reasons explain Esther’s loathing are, first, her mother discouraged Esther from mourning over her dead father, and, second, Esther sees her mother as a woman who sacrificed her will for her husband’s career. Esther’s memories of her father are distressing. Her father died when Esther was nine, and she was forbidden to mourn his passing. Neither she nor her mother were perceived to have grieved over their loss, although the grieving process represents a necessary psychological part of coping with a death and without it, one could suffer from depression just as Esther does. Esther illustrates the complex patterns of what one’s memory can give to a young woman who abstains from the assumed roles of domesticity. The memory of Esther’s father plays a prominent part in the story with regards to her resistance to cultural conditioning and the role of domesticity. The memory insists on gradually closing her mind until it is locked in a state of containment. Esther resists fitting into the social norms around her, especially the dreaded idea of domesticity. Her resistance to a normative lifestyle, the key which develops into her alienation, traces back to Esther’s memory of her father. Hence, Esther’s alienation becomes increasingly apparent when she links her emptiness to the death of her father. The memory of Esther’s father resurfaces multiple times in the novel to demonstrate how his death possesses a tight hold on her, which relates to her resistance to a normative domestic lifestyle and contributes to her alienation. ESTHER GREENWOOD’S PARTICIPATION: A STRATEGY TO COPE WITH ALIENATION An alienated person needs to find work or activities which one believe will lead to worthy rewards. But beyond this, the alienated person needs to find and maintain sources of natural production and association/participation—meaningful activities and loving relationships. This is a part of both social and psychological matter. It may also require changes in a person’s ways of perceiving and thinking about work and people and themselves. Even though Esther sometimes stands apart from other women and describes herself as alienated, she participates in moments of what so called group laughter. For example, when Esther is recovering in the hospital from ptomaine poisoning (which occurs as the result of the failure of Ladies’ Day banquet), Doreen comes to care for her and temporarily sheds her stereotyped bombshell identity. In this moment of sisterly alliance, Esther and Doreen “both burst out laughing” (Plath, 1963: 49) about the gifts that they have received from Ladies’ Day. Though Esther mocks Doreen at other times in the story, this instance of healthy participation allows them to recognize their shared relationship to the culture of female beauty that the magazine, where they do the internship, stands for. Esther’s road to recovery—including the institutionalization—is apparent in the second half of The Bell Jar. Through the financial intervention of a benefactor, Esther is taken to a mental institution with private psychiatric. There, Esther begins gradually to recover. She enjoys the plesant country-club surrounding and develops a closeness with her analytically psychiatrist, Dr. Nolan. During her recovery in the mental institution, a similar case occurs as that had happened with Doreen. Esther is committed to a mental institution as a period of recovery for her mental illness. Esther notes that other women who as well stay in the mental institution “kept tossing back and forth these private jokes” (Plath, 1963: 205). Although Esther feels excluded from this circle of friends there, she observes how DeeDee and Loubelle join together by cracking jokes at their husbands’ expense. In joking about their common problems, DeeDee and Loubelle show a miniature community in the form of solidarity. Even when women in the story do not appear entirely tender toward one another, they can still form this sense of solidarity. Although Esther frequently mocks other women and even highlights her own shortcomings, her goal is not to belittle women or to make jokes at their expense. Rather, she turns to dark humor and cynical in an attempt to excise the influence of the feminity, as she repeatedly emphasizes that imitating media stereotypes evacuates women of their freedom. Likewise, when she transforms her feelings of passivity into cynical, she draws attention to the way in which American women in her era feel “brainwashed” and “numb” (Plath, 1953: 85). This development of community helps those women to recognize that their mental illness might stem from a larger crisis in femininity, and not simply from their own deficiencies. It allows the women to begin to feel less alone in their bewilderment about their roles and responsibilities. In this respect, Dr. Nolan is integral to Esther’s recovery. Dr. Nolan is a direct yet humane psychiatrist who empowers Esther. She appears to play a special role in Esther’s recovery on coping with alienation. Not simply because of her role as a psychiatrist but because, with her supportive smile, she fulfills a function similar to the community. Combining the attributes of defined femininity and professional accomplishment, Dr. Nolan is set forth as an ideal role model for Esther. The trust she puts on Esther, which undoubtedly counts for a great deal. Through Dr. Nolan’s influence, Esther comes to understand her own motivations and reconciles with her anger. Not judgmental, she empowers Esther by not criticizing or analyzing her hatred feeling toward her mother. It shows when, with the help of Dr. Nolan, Esther makes a startling discovery about her relationship with her mother: “’I hate her,’ I said, and waited for the blow to fall” (Plath, 1963: 203). Esther expects the doctor to rebuke her for this outburst, but instead, Dr. Nolan smiles at her as if pleased. Dr. Nolan reacts with satisfaction, as if this admission explains Esther’s condition and marks an important step in her recovery. Dr. Nolan recognizes that Esther has identified a root cause of her alienation. She is encouraged that Esther is now speaking openly about her feelings, instead of hiding behind a wall of apathy. This is important, for it shows that Esther is becoming more emotional and less fatalistic. It appears that Esther’s hatred for her mother stems from her own fear of ending up like her, entrapped in a conventional life, performing typewriting, and hence becoming the ultimate copying machine. Therefore, Dr. Nolan notably does not critique Esther or downplay her mental illness, but offers her the kind of “tenderness” that “women see in other women” (Plath, 1963: 219). Else than that, during her recovery in the mental institution, there are two meaningful relations with women which are open to Esther. First is obviously the relation with her psychiatrist, Dr. Nolan, and, second, her friend, Joan Gilling. Joan and Esther represent the two most complex characters in The Bell Jar and share many similarities. Both attend a prestigious women’s college; both are intelligent, accomplished women; both come from the same hometown and went to the same church; both have suicidal tendencies. Further, both come to despise Buddy Willard for similar reasons and she is admitted to the same mental institution as Esther. What distinguishes Joan and Esther most obviously is money. Joan comes from a wealthy family, whereas Esther’s background is modestly middle class. Hence, Joan takes for granted many things—horseback riding, fancy clothes, private lessons—that Esther must struggle to obtain. Regardless their social status, Joan Gilling is such a character in the story whom Esther considers the half part of her existence. It is as if Esther finds a sense of completion in her scattered identity on the figure of Joan. Like her attitude toward most of the major female characters in the novel, Esther is ambivalent toward Joan. Esther discovers that Joan is a lesbian, and when Joan says that she likes Esther, Esther reacts negatively and walks out of the room. The relationship between Esther and Joan is terminated decisively by the Joan’s suicide, and somehow it changes Esther’s prior rejection of that character. In one the scene of the story, Esther attends Joan’s funeral and she comes to a realization. At this moment when Joan finally commits suicide, Esther believes that unless she turns her life around, she will also commit suicide and end up like Joan. Esther sees so much of herself in Joan, that when Joan ends her life, she is also frightened that she will follow in her footsteps, due to the fact that she had throughout the entire story. However, after the funeral, Esther becomes aware of her own recovery and newly identified self. She comes to recognize her new relation between her sense of self and reality. Esther’s new affirmation of life is clear when she listens “to the old brag of my heart” and convinces herself that she is alive by hearing “I am I am I am” of the heartbeat (Plath, 1963: 233). The heartbeat seems to make a statement about the mind and body both have a will to live. It is a proof that now, she embraces life rather than protests against it. Esther also asks Dr. Nolan if she should feel responsible for Joan’s death, and Dr. Nolan assures that no one is to blame for Joan’s death, least of all Esther. However it demonstrates that Esther can now empathize with others, and think of something other than her own pain. This funeral seems to be not only a funeral for Joan, but may also be seen as Esther’s own symbolic funeral, her farewell to her troubled past. It is as if the depressive side of Esther’s own self has been destroyed. Although, it is also ironic that Joan, with all her social status and economic advantages, destroys herself, while struggling Esther is the survivor. Through the female solidarity with mutual equality between Esther and Dr. Nolan, Esther gradually recovers from her mental illness and view the path she would like to choose for her life. In the other hand, by communication with Joan Gilling, the mirroring self, Esther is no longer directionless to resist the society norm control and starts to gain the female individuality with unprecedented courage and confidence. Esther is getting stronger and is able to think more clearly than before. As she begins to search for a stable sense of identity, she makes some constructive choices. She rejects a possible alternative of homosexuality when she sees it in Joan. Lesbianism has no appeal for her. She also rejects Buddy because she still regards him as a hypocrite. The conventional kind of marriage, in which she is housewife to a handsome doctor, does not appeal to her as well. She has no maternal instinct and does not want children. Furthermore, Esther still seeks to lose her virginity after all the endurance in her life. Here, Esther’s opposition is clearly seen when afther having an approval from Dr. Nolan, she goes to a clinic and gets fitted for a diaphragm. This gives her a sense of freedom from men. Now she can seek sexual experience without having to worry about pregnancy. Her acquisition of birth control represents a step toward emancipation from the limited, dependent role ascribed to her as a woman. Esther is free at the end for having lost her virginity by having her first sex—although her hemorrhaging (cannot stop bleeding after losing virginity) becomes a near-death experience. For this her first sexual experience, Esther once again asserts her freedom by deliberately choosing a proper man in whom she uses him solely for the sake of sex itself. Esther also recovers her emotional balance. She shows she is aware of the suffering she caused her mother: “A daughter in an asylum! I had done that to her” (Plath, 1963: 237), whereas before all she could feel was her hatred for her mother. She also recognizes that her mother has decided to forgive her: “Still, she had obviously decided to forgive me” (Plath, 1963: 237). Although Esther appears to soften her view as she recovers, she sharply disagrees with her mother about how to reestablish her life. She cannot accept her mother’s desire to “act as if all this were a bad dream” (Plath, 1963: 237). Esther knows better, however. She is prepared to face up to reality, knowing that her experience of mental breakdown is a part of her experience of life: “They were my landscape” (Plath, 1963: 237). She cannot simply pretend it never happened. In this respect, Esther shows a more mature awareness than her mother. But while she recognizes continuity with her past, she also shows that she is ready to move on to a new phase. When Buddy visits her, for example, he seems “small and unrelated to me” (Plath, 1963: 238). With Esther’s uphill climb in life at the point in the mental institution and her psychiatrist’s encouragements, the predicted result of this interview is certainly positive. The ending is hopeful. With the open ending, Plath is implying things do not simply end at the end of the novel. Although Esther might continue to encounter difficulties, she may always overcome it like this time. And although very little has changed for Esther with regard to her relationships with family and friends, however, what the most important thing is Esther’s ability to cope and face the challenges that these may provide her. Esther may fear the reoccurrence of her bell jar, but even so, she can break free of it. She has done it once, it can always be overcome. Once the recipe for being happy is discovered, following it is much easier. The bell jar is finally lifted. CONCLUSION Based on the previous analysis upon Esther Greenwood’s alienation in Sylvia Plath’s The Bell Jar, there can be identified some important finding facts. This includes Esther Greenwood’s alienation depicted in the story, as well as the root cause of her alienation and how Esther Greenwood copes with it. The first conclusion is related to the occurrence of Esther Greenwood’s alienation depicted in the story. In this case, Esther Greenwood’s alienation manifest in five senses; those are powerlessness, meaninglessness, normlessness, isolation, and self-estrangement. Esther’s alienation in the sense of powerlessness can be seen on her jealousy of unable to experience such luxuries which the other girls have, since Esther is only raised in the middle-social-background family. This sense of powerlessness traps Esther into jealousy to socially estranged. Esther feels overwhelmed and powerless to break free the emotional burdens of status and social class difference. Esther’s alienation in the sense of meaninglessness makes Esther feel all of her working life seems dominated by piles of meaningless manuscripts, compared the way that people around her are living it in luxury, the thing that she never has. As a result, Esther does not find any purpose and goal to even act any single action as she feels indecisive all the time. Furthermore, Esther’s alienation in the sense of normlessness appears when she is against the conventional attitude of what a woman’s place in society is. It can be seen that Esther, unlike many women of her time, refuses to be controlled by society’s gender-based constraints. She decides not to marry, not to have children, to have sexual freedom, and to be a different kind of woman than what the society norm would wish for. She is so determined where her concerns are different, as well as her obstacles, especially in the general of social-ethos in 1950s America. In the other side, Esther’s isolation is implicitly depicted even on the meaning of the title The Bell Jar itself. Plath chooses this imagery which holds a perfect key to reveal Esther’s isolation. Here, the bell jar is viewed as a symbol of society’s stifling constraints and confusing mixed messages that trap Esther within its glass dome. Esther has her own “bell jar”, where she feels isolated all the time. To complicate the matters more, Esther’s sense of isolation is worsen when she loses interest in both social life and her work. The last but not least is Esther’s alienation in the sense of self-estrangement. This is where Esther herself unsure about her true identity. She has sense of inner absence, vacuity, a loss of self or estrangement from a familiar and recognizable self. And thus she becomes a stranger in society and, more importantly, to herself. The more self-estranged Esther becomes, the less attached she is to her real wants, needs, hopes, and dreams. As a result, this sense of self-estrangement prevents Esther to find a real joy in life. The second conclusion that can be drawn regarding to Esther Greenwood’s alienation is related to Esther’s attempts on coping with her alienation. In this case, the first attempt is depicted when Esther finally discovers the root cause of her alienation. It shows that Esther’s alienation has multiple causes; including the era’s “domestic containment” of women and her fraught relationship with her parents. Esther’s domineering boyfriend, Buddy Willard, ignores Esther’s attempts to vision a future in which she is not even his wife. Instead of supporting her, Buddy prevents Esther from exploring alternate possibilities for her future and has her to be in the world of domesticity. Similar to Buddy, Esther’s mother, Mrs. Greenwood, though superficially caring and picture perfect, functions as a subtle force of control and reproach. Esther’s mother insists that her daughter channel herself into socially acceptable directions without paying attention to her own needs. As a result, Esther is ambivalent toward her mother. She even says that she hates her mother. Two reasons which also explain Esther’s loathing are, first, her mother discouraged Esther from mourning over her dead father, and, second, Esther sees her mother as a woman who sacrificed her will for her husband’s career. The third and last conclusion that can be made is still regarding to Esther Greenwood’s attempts on coping with alienation. In this case, it is related to Esther’s participation in community. This second attempt to cope with alienation is shown when Esther is institutionalized and treated for her mental illness. There, she develops a form of community with the other women who stay in the institution. This development of community helps those women to recognize that their mental illness might stem from a larger crisis in femininity, and not simply from their own deficiencies. It allows the women to begin to feel less alone in their bewilderment about their roles and responsibilities. This shows a miniature community in the form of what so called solidarity. And this also is one of strategy to cope with alienation. Else than that, during Esther’s recovery in the mental institution, there are two meaningful relations with women which are open to Esther. First is the relation with her psychiatrist, Dr. Nolan, and, second, her friend, Joan Gilling which both bring her comforts in each particular way. Through the female solidarity with mutual equality between Esther and Dr. Nolan, Esther gradually recovers from her mental illness and view the path she would like to choose for her life. In the other hand, by communication with Joan Gilling, the mirroring self, Esther is no longer directionless to resist the society norm control and starts to gain the female individuality with unprecedented courage and confidence. Furthermore, after much endurance of life in a bell jar, Esther is as well free at the end for having lost her virginity by having her first sex, since she believes losing her virginity will finally result in her freedom from the pureness burden. Moreover, Esther also recovers her emotional balance. While she recognizes continuity with her past, she also shows that she is ready to move on to a new phase. The Bell Jar ends with open interpretation. But with Esther’s uphill climb in life at the point in the mental institution with her psychiatrist’s encouragements, it is assumed that the ending is hopeful. Esther recovers and finally leaves the mental institution to face the world once again. Although until the very end of the story nothing of conventional rule in society changes, but once Esther’s views change, it is when the bell jar lifts. REFERENCES Francisco, Rolyn B. 1995. “Karol Wojtyla’s Theory of Participation”. Makati: St. Paul’s. In Dean Edward A. Mejos (Ed.). Against Alienation: Karol Wojtyla’s Theory of Participation. Vol. 1, No. 1, June 2007, pp. 71-85. Fromm, Erich. 1955. The Sane Society. New York: Fawcet World Library. Heidegger, Martin. 1962. “Being and Time”. Translated by J. Macquarrie and E. Robinson. Oxford: Blackwell. In Sean Sayers (Ed.). The Concept of Alienation in Existentialism and Marxism Hegelian Themes in Modern Social Thought. (Retrieved March 23, 2014, from Error! Hyperlink reference not valid.alienation.pdf) Hargrove, Nancy Duvall. 1980. “Sylvia Plath.” American Novelist Since World War II: Second Series. Ed. James E. Kibler. Dictionary of Literary Biography Vol. 6. Detroit: Gale Research (Retrieved April 13, 2014 from http://www.examiner.com/article/sylvia-plath-an-analysis-of-the-bell-jar) MacIntyre, Alasdair. 1981. “After Virtue: A Study in Moral Theory”. London: Duckworth. In Sean Sayers (Ed.). 1996. Identity And Community. University of Kent at Canterbury. (Retrieved April 13, 2014, from Error! Hyperlink reference not valid.sayers/identity.pdf) Parsons, Deborah. 2007. Theorists of the Modernist Novel. New York: Routledge Critical Thinkers. Perloff, Marjorie G. 1999. “A Ritual for Being Born Twice: Sylvia Plath’s The Bell Jar”. In Contemporary Literature, Vol. 13, No. 4, Autumn, 1972, pp. 507-522. All rights reserved by The Gale Group. (Retrieved April 13, 2014, from (http://www.sylviaplath.de/plath/perloff. html) Plath, Sylvia. 1963. The Bell Jar. New York: Harper & Row. Ratna, Nyoman Kutha. 2004. Teori, Metode, dan Teknik Penelitian Sastra. Yogyakarta: Pustaka Pelajar. Seeman, Melvin. 1959. “On The Meaning Of Alienation”. Los Angeles: University Of California. In American Sociological Review, Vol. 24, No. 6 (Dec., 1959), pp. 783-791. Tabrizi, Mohseni, & Reza, Ali. 1991. “Alienation, Social Science Letter”. Vol. 2. No. 2. University of Tehran press. In Mahmoud Elmi (Ed.). 2012. Social Alienation and Identity Status. (Retrieved March 23, 2014, from http://www.lifesciencesite .com) Wojtyla, Karol. 1979. “The Acting Person”. Translated by Andrej Potocki. Dordrecht: D. Reidel Publishing Company. In Dean Edward A. Mejos (Ed.). Against Alienation: Karol Wojtyla’s Theory of Participation. Vol. 1, No. 1, June 2007, pp. 71-85. ____________. 1993. “Love and Responsibility”. Translated by H.T Willets. San Francisco: Ignatius Press. In Dean Edward A. Mejos (Ed.). Against Alienation: Karol Wojtyla’s Theory of Participation. Vol. 1, No. 1, June 2007, pp. 71-85.